(untitled) (Jurnal Pustaka, 2026)
FTAs represent instances where communication potentially threatens one‟s self-image or social standing. This research analyzes the types of Face-Threatening Acts (FTAs) in the film “Never Rarely Sometimes Always,” categorizing them according to Brown and Levinson‟s theory: Threatening Hearer‟s Negative Face, Threatening Hearer‟s Positive Face, Threatening Speaker‟s Negative Face, and Threatening Speaker‟s Positive Face. This study also examines the politeness strategies used to mitigate FTAs, considering situational context factors outlined by Holmes. This study used qualitative and descriptive methods, and data was collected through documentation and note-taking, classifying utterances based on FTAs and politeness strategies. This study found that the most common FTA in the object of this study is threatening the hearer‟s negative face by making requests, advice, suggestions, compliments, offers, and orders. The threats to the hearer‟s positive face included disagreements, insults, ridicule, emotional topics, reprimands, and taboo topics. FTAs towards the speaker‟s face included expressing thanks, accepting offers, accepting apologies, apologies, and receiving compliments. Characters in the film used Positive Politeness and Negative Politeness strategies to mitigate FTAs.